Impact of the COVID-19 Pandemic on Audit Quality: Lessons and Opportunities - Saddam A. Hazaea; Mosab I. Tabash; Abdul Aziz Abdul Rahman; Saleh F. A. Khatib; Jinyu Zhu; H Gin Chong (Emerging Science Journal, 2022)
This study aims to identify the impact of COVID-19 on audit quality based on the investigation of three auditing aspects, namely: audit fees, audit procedures, and auditors' salaries in Saudi Arabia and Yemen. For data collection, fifty-five (55) questionnaires were distributed to internal auditors, external auditors, managers of audit offices, and financial managers. Eleven managers of audit offices and auditors were interviewed. A descriptive, regression analysis, and T-test were used. The study results reveal that the audit quality has been significantly affected due to the devastating effect of COVID-19 on audit fees, audit procedures, and audit staff salaries. In addition, the results show that Yemen is severely affected due to several factors, which include a lack of modern auditing systems. Also, private ownership of establishments and the absence of laws for determining audit fees negatively impacted the audit quality. Being the first of a practical kind, this study provides a significant contribution to the existing literature on the impact of COVID-19 on the quality of auditing. This would be useful for corporations, audit offices, auditors, and researchers. Moreover, this study can bridge the identified research gap on this topic and provide empirical evidence about the impact of COVID-19 on audit quality. Doi: 10.28991/esj-2022-SPER-06 Full Text: PDF